(untitled) (International Journal of Engineering and Computer Science, 2017)
Data mining is the procedure of mining knowledge from data. This is extensively studied field for research area, where most of the work emphasized over knowledge discovery. Outlier detection is an important task in data mining and it has many real time applications . In most of the applications data contains unwanted and unrelated data. Finding and removing anomalous data is very important and there by improve the quality and accuracy. The outliers are pinpoint or group that depends on data and applications. This paper focus on outlier concept, taxonomy and outlier detection using least square fit